Development Change in the Optional Handicraft (Technology) Training in Lithuania - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 2005)
This article reveals development change in the optional handicraft (technology) training. Extracurricular activities development organization peculiarities are discussed comparing two different periods (Soviet and restored independence). The reasons, which make extracurricular activities hardly approachable, are emphasized. The research showed that in 1947-1989 extracurricular activities in republic schools were not always qualified enough, moreover, smoothly and creatively organized, even though a lot of efforts were put in order to prepare schoolchildren for practical work activities. Now extracurricular activities are being developed: it is necessary to renew schools material base, to improve the financial position and the pedagogues preparation.